Malformasi Rangka Fetus Tikus Wistar Akibat Efek Teratogenik Insektisida Endosulfan (SKELETAL MALFORMATION OF WISTAR RAT FETUSES DUE TO THE TERATOGENIC EFFECT OF ENDOSULFAN INSECTICIDE) - Malini, Desak Made; Madihah, Madihah; Shalihah, Amalia (Jurnal Veteriner, 2017)
Endosulfan an organochlorine insecticide that is commonly used even though it has been banned due to its toxic and teratogenic effect. This study aims to determine the effect of orally endosulfan exposure to pregnant rat ( Rattus norvegicus ) at day 6-15th of gestation period to the foetus skeletal malformation. A Completely Randomized Design (CRD) by endosulfan dosages: 0 (control); 0.083; 0.190; 0.440; 1.000 mg/kg BW/day with 5 replicates was applied. At 20th of the gestational period, the rats were sacrificed, their reproductive organs and the fetal skeletal malformation were observed using Alizarin red S method. The results of one-way ANOVA test showed that endosulfan exposure did not significantly affect the pregnancy outcomes ie. female rats weight gain, the numbers of implanted foetus, foetal body weight and length, respectively. Malformation of foetus implantation, foetus size and foetus skeletal occured in the endosulfan exposure groups. Fisher’s exact test results showed a significant difference between the control group and the endosulfan exposure group on the number of foetuses that have abnormalities in the number of skeletons of the sternum, fore and hind paws. The exposure of endosulfan at 0.083-1.000 mg / kg BW / day in pregnant rats caused skeletal malformations of the foetus ie. decreased in the number on sternum, fore- and hind paw bones. ABSTRAK Endosulfan merupakan insektisida golongan organoklorin yang masih digunakan hingga kini meski telah dilarang karena bersifat toksik dan teratogenik. Penelitian ini bertujuan untuk mengetahui efek pemajanan endosulfan secara oral terhadap malformasi rangka fetus tikus ( Rattus norvegicus Berkenhout, 1769) selama umur kebuntingan 6-15 hari. Penelitian dilakukan secara eksperimental di laboratorium menggunakan Rancangan Acak Lengkap (RAL) dengan pemajanan endosulfan dosis: 0 (kontrol); 0,083; 0,19; 0,44; dan 1 mg/kg BB/hari dan masing-masing diulang sebanyak lima kali. Induk betina dengan umur kebuntingan 20 hari, dikorbankan nyawanya lalu dibedah dan diamati tampilan reproduksi induk serta malformasi rangka pada fetus dengan metode pewarnaan Alizarin red S . Hasil uji sidik ragam satu arah menunjukkan pemajanan endosulfan tidak berpengaruh secara signifikan terhadap rataan pertambahan bobot badan induk, jumlah fetus terimplantasi, bobot badan dan panjang fetus. Malformasi implantasi fetus, ukuran fetus dan rangka fetus terjadi pada kelompok pemajanan endosulfan. Hasil uji eksak Fisher menunjukkan adanya perbedaan yang signifikan antara kelompok kontrol dengan kelompok pemajanan endosulfan terhadap jumlah fetus yang mengalami kelainan jumlah rangka penyusun sternum, cakar depan dan cakar belakang. Simpulan dari penelitian ini adalah pemajanan endosulfan dosis 0,083- 1,000 mg/kg BB/hari pada tikus bunting menimbulkan malformasi rangka pada fetus yaitu berkurangnya jumlah tulang penyusun sternum, cakar depan, dan cakar belakang.